1993
DOI: 10.1002/ajmg.1320460408
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific immunity in down syndrome: A study of chemotaxis, phagocytosis, oxidative metabolism, and cell surface marker expression of polymorphonuclear cells

Abstract: We have investigated several aspects of nonspecific immunity in Down syndrome (DS), utilizing peripheral polymorphonuclear leukocytes (PMNL), obtained from 12 children aged 8-16, diagnosed as trisomy 21, and their healthy matched controls. We used the under agarose method for chemotaxis assays, and flow cytometry for the determination of phagocytosis of monodispersed fluorescent beads, metabolic burst activity, and neutrophil surface marker expression on these cells. Our results indicate that a chemotactic def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…Children with DS are highly susceptible to infection and the tendency towards an impaired immune system has been well documented. Observed defects in immune function include decreased white cell counts, impaired cell-to-cell communication, reduced antibody levels, and abnormal lymphocyte function (Fong and Brodeur, 1987;Novo et al, 1993). In the presence of proliferative leukocyte stress provoked by infection, inherently abnormal leukocyte stem cells in patients with DS may be at increased risk of a second mutation resulting in leukaemia (Stewart, 1961).…”
Section: Discussionmentioning
confidence: 99%
“…Children with DS are highly susceptible to infection and the tendency towards an impaired immune system has been well documented. Observed defects in immune function include decreased white cell counts, impaired cell-to-cell communication, reduced antibody levels, and abnormal lymphocyte function (Fong and Brodeur, 1987;Novo et al, 1993). In the presence of proliferative leukocyte stress provoked by infection, inherently abnormal leukocyte stem cells in patients with DS may be at increased risk of a second mutation resulting in leukaemia (Stewart, 1961).…”
Section: Discussionmentioning
confidence: 99%
“…These associated disorders have been attributed to immunodeficiency and increased susceptibility to acute infections [Spina et al, 1981;Burgio et al, 1983]. In addition, decreased microbicidal activity [Novo et al, 1993] and deficient chemotaxis [Khan et al, 1975;Novo et al, 1993] in neutrophil functions are observed in DS patients. Increased morbidity of DS patients results from respiratory and gastrointestinal infections with a high incidence of heart failure and malignancy [Miller, 1971;Masaki et al, 1981].…”
Section: Introductionmentioning
confidence: 96%
“…Several risk factors for influenza also occur in Down syndrome patients ( 2 ): congenital heart disease in one half of patients ( 3 ), childhood obesity or excess weight in the majority ( 4 ), and a 8× higher prevalence of type 1 diabetes than in an age-matched control population ( 5 ). In addition, specific alterations in immune response are frequently present, including leukopenia, chemotactic defects ( 6 ), decreased immunoglobulin G 4 levels ( 7 ), and T- and B-cell abnormalities ( 7 , 8 ) with reduced B lymphocytes ( 9 ). Patients with Down syndrome have an increased need for hospitalization because of lower respiratory tract disease caused by respiratory syncytial virus ( 10 ) and other respiratory infections ( 11 ) as well as reduced access to healthcare ( 12 ).…”
mentioning
confidence: 99%